2009
DOI: 10.1117/1.3253382
|View full text |Cite
|
Sign up to set email alerts
|

Repetition rate dependency of reactive oxygen species formation during femtosecond laser–based cell surgery

Abstract: Femtosecond (fs) laser-based cell surgery is typically done in two different regimes, at kHz or MHz repetition rate. Formation of reactive oxygen species (ROS) is an often predicted effect due to illumination with short laser pulses in biological tissue. We present our study on ROS formation in single cells in response to irradiation with fs laser pulses depending on the repetition rate while focusing into the cell nucleus. We observed a significant increase of ROS concentration directly after manipulation fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
15
0
1
Order By: Relevance
“…Membrane damage might be supported by repetitive stress from a number of small vapor bubbles or be induced via biochemical effects such as oxidative stress from generation of reactive oxygen species or release of intracellular Ca 2+ . Such biochemical effects have been reported for ultrasound exposure [37] and fs-pulse irradiation [38,39] and may occur upon exposure to ns-pulse induced vapor bubble formation in the immediate vicinity of cell organelles. However, we believe that the most important reason for the lower damage threshold under multiple pulse exposure is related to the change in position of the nanoparticles.…”
Section: Discussionmentioning
confidence: 75%
“…Membrane damage might be supported by repetitive stress from a number of small vapor bubbles or be induced via biochemical effects such as oxidative stress from generation of reactive oxygen species or release of intracellular Ca 2+ . Such biochemical effects have been reported for ultrasound exposure [37] and fs-pulse irradiation [38,39] and may occur upon exposure to ns-pulse induced vapor bubble formation in the immediate vicinity of cell organelles. However, we believe that the most important reason for the lower damage threshold under multiple pulse exposure is related to the change in position of the nanoparticles.…”
Section: Discussionmentioning
confidence: 75%
“…Nikogosyan et al showed that photochemical processes leading to generation of ROS in aqueous solution can be classified into fast and slow reactions with time constants in the nano- to microsecond and millisecond range, respectively [21]. Recent experimental studies by our group revealed an influence of the laser repetition rate on the efficiency of ROS formation in cells and tissue [25, 26]. Consequently, the time interval between two successive laser pulses may affect the ablation threshold of subcellular structures.…”
mentioning
confidence: 99%
“…Fluorescence methods already have been successfully utilized for confirming the optical transfection of cells (see e.g. [15][16][17]) but this requires a cell modification or sensing with specific dyes which may be toxic. Furthermore, a maximized performance of fluorescence imaging needs a precise focussing of the sample which becomes in particular a challenge in combination with multiple optical tweezers and microfluidics.…”
Section: Biophotonicsmentioning
confidence: 99%